The Relationship Between Market Share and Profitability of Ghanaian Banks - Kulu, Evans; Appiah-Kubi, Grace Darko (International Journal of Business, Economics and Management, 2021)
As an important indicator of banks’ performance, market share has been of interest to researchers and managers owing to its contribution to profitability and the variations in the face of the banking sector. This study aims at revealing the various factors that affect the market share of banks in Ghana and examine its relationship with profitability. We employ the fixed and random effect as well as the system General Methods of Moments estimation techniques on panel data for 12 banks in Ghana. The results from this study show that non-performing loans and liquidity are significant determinants and relate negatively with the market share of banks while leverage and bank size are also significant determinants but relate positively with the market share of these banks. The study further revealed that market share positively and significantly affects the profitability of banks. Banks are therefore recommended to adopt ways such as innovation, strengthening of customer relationships, and smart hiring practices that will help them increase their market share to improve on the performance and profitability of the banks.